Culturable Bacterial Microbiota of the Stomach of Helicobacter pylori Positive and Negative Gastric Disease Patients. (6th July 2014) - Khosravi, Yalda; Dieye, Yakhya; Poh, Bee Hoon; Ng, Chow Goon; Loke, Mun Fai; Goh, Khean Lee; Vadivelu, Jamuna
Abstract : Human stomach is the only known natural habitat of Helicobacter pylori ( Hp ), a major bacterial pathogen that causes different gastroduodenal diseases. Despite this, the impact of Hp on the diversity and the composition of the gastric microbiota has been poorly studied. In this study, we have analyzed the culturable gastric microbiota of 215 Malaysian patients, including 131 Hp positive and 84 Hp negative individuals that were affected by different gastric diseases. Non- Hp bacteria isolated from biopsy samples were identified by matrix assisted laser desorption ionization-time of flight mass spectrometry based biotyping and 16SrRNA sequencing. The presence of Hp did not significantly modify the diversity of the gastric microbiota. However, correlation was observed between the isolation of Streptococci and peptic ulcer disease. In addition, as a first report, Burkholderia pseudomallei was also isolated from the gastric samples of the local population. This study suggested that there may be geographical variations in the diversity of the human gastric microbiome. Geographically linked diversity in the gastric microbiome and possible interactions between Hp and other bacterial species from stomach microbiota in pathogenesis are proposed for further investigations.